Is Zimbabwe ready to transition from anonymous unlinked sero-surveillance to using prevention of mother to child transmission of HIV (PMTCT) program data for HIV surveillance?: results of PMTCT utility study, 2012 - Gonese, E. (BMC Infect Dis, 2016)
BACKGROUND: Prevention of mother-to-child transmission of HIV (PMTCT) programs collect socio-demographic and HIV testing information similar to that collected by unlinked anonymous testing sero-surveillance (UAT) in antenatal settings. Zimbabwe evaluated the utility of PMTCT data in replacing UAT. METHODS: A UAT dataset was created by capturing socio-demographic, testing practices from the woman’s booking-card and testing remnant blood at a laboratory from 1 June to 30 September 2012. PMTCT data were collected retrospectively from ANC registers. UAT and PMTCT data were linked by bar-code labels that were temporarily affixed to the ANC register. A questionnaire was used to obtain facility-level data at 53 sites. RESULTS: Pooled HIV prevalence was 15.8 % (95 % CI 15.3–16.4) among 17,349 women sampled by UAT, and 16.3 % (95 % CI 15.8 %–16.9 %) among 17,150 women in PMTCT datasets for 53 sites. Pooled national percent-positive agreement (PPA) was 91.2 %, and percent-negative agreement (PNA) was 98.7 % for 16,782 women with matched UAT and PMTCT data. Based on UAT methods, overall median prevalence was 12.9 % (Range 4.0 %–19.4 %) among acceptors and refusers of HIV test in PMTCT compared to 12.5 % ((Range 3.4 %–19.5 %) among acceptors in ANC registers. There were variations in prevalence by site. CONCLUSION: Although, there is no statistical difference between pooled HIV prevalence in UAT compared to PMTCT program, the overall PPA of 91.2 % and PNA of 98.7 % fall below World Health Organisation (WHO) benchmarks of 97.6 % and 99.6 % respectively. Zimbabwe will need to strengthen quality assurance (QA) of rapid HIV testing and data collection practices. Sites with good performance should be prioritised for transitioning. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12879-016-1425-2) contains supplementary material, which is available to authorized users.